SOURCES OF INFLUENCE OF THE NOVEL "SPITAMEN" - Mamurova Mushtari Makhammadjanovna (International Scientific and Current Research Conferences, 2022)
The article contains the analysis of Maqsud Qariev's novel "Spitamen", the sources of influence in writing it, the creation of the image of Spitamen, the interpretation of the tragic history of our nation.